An AI-based decision support system for designing Knowledge-Based Development strategies. (6th May 2008) - Ergazakis, Emmanouil; Ergazakis, Kostas; Metaxiotis, Kostas; Bellos, E.; , V. Leopoulos
In the new era of knowledge economy, knowledge and the processes to generate and manage it are considered as the most valuable assets of an organisation in the competitive business environment. Over the last years, intensive discussions have taken place about the importance of Knowledge Management for the whole society, except from the business world. Today, there is a consensus among researcher's and practitioner's communities that the challenges facing modern societies, call for development strategies that are knowledge-based. In this context, the theme of Knowledge Cities (KCs) came to the front. The review of literature reveals that the process of designing Knowledge-Based Development (KBD) strategies for KCs is complex and not appropriately supported by decision support methodologies and/or intelligent systems. In this paper, the authors, based on a previously presented methodology for the formulation of a KBD strategy for KCs, propose an AI-based decision support system for designing such strategies, by selecting and prioritising the most appropriate interventions and actions. The system consists of two sub-systems: the first (developed using the technology of Expert Systems) assess the necessity of a particular intervention and proposes its most appropriate form. The second prioritises the selected interventions based on Multi-Criteria Decision Making. The authors also present the successful preliminary results of the system?s pilot application to a Greek municipality.